2015
DOI: 10.1111/bcp.12474
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions – examples of detection of rare events using databases

Abstract: It is recognised that randomised controlled trials are not feasible for capturing rare adverse events. There is an increasing trend towards observational research methodologies using large population‐based health databases. These databases offer more scope for adequate sample sizes, allowing for comprehensive patient characterisation and assessment of the associated factors. While direct causality cannot be established and confounders cannot be ignored, databases present an opportunity to explore and quantify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Observational studies have demonstrated a higher incidence of cardiovascular events such as arrhythmia and sudden death in patients treated with methylphenidate or other stimulants, as compared to controls. Yet, this finding has not been confirmed in other studies . However, there is sufficient evidence suggesting a potential relationship between stimulants and cardiovascular risk.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Observational studies have demonstrated a higher incidence of cardiovascular events such as arrhythmia and sudden death in patients treated with methylphenidate or other stimulants, as compared to controls. Yet, this finding has not been confirmed in other studies . However, there is sufficient evidence suggesting a potential relationship between stimulants and cardiovascular risk.…”
Section: Discussionmentioning
confidence: 57%
“…Yet, this finding has not been confirmed in other studies. 15,21 However, there is sufficient evidence suggesting a potential relationship between stimulants and cardiovascular risk.…”
Section: Background Of Published Studiesmentioning
confidence: 99%
“…Another issue might be reporting bias [93] and attitudes of clinicians may unconsciously influence the reporting of adverse events. Rigorous research methodologies using large population-based health databases should help do address some of these limitations [94]. Data linkage of medication data and the onset of specific predefined clinical events supported by large integrate electronic medical records [95] should enable clinicians and regulators to identify potential adverse events without clinical reporting bias.…”
Section: Discussionmentioning
confidence: 99%
“…adverse event reporting systems) and are occasionally mandated by regulators if there is an inconclusive safety signal in pre‐licensing RCTs . Observational studies can facilitate the detection of rare (<1/1000) and very rare (<1/10 000) adverse events (see Table ) and are also able to provide long‐term data on tolerability …”
Section: Observational Pharmacoepidemiologymentioning
confidence: 99%
“…88 Observational studies can facilitate the detection of rare (<1/1000) and very rare (<1/10 000) adverse events (see Table 3) and are also able to provide long-term data on tolerability. 83,89 Since observational studies frequently run in parallel with routine clinical care, they often cost less than RCTs. 90…”
Section: Op Studies Can Be Carried Out Over a Long Period Of Time mentioning
confidence: 99%